2009
DOI: 10.1016/s1658-3876(09)50037-4
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of allogeneic peripheral blood stem cell versus bone marrow transplantation

Abstract: Although allogeneic PBSC transplant results in a faster hematopoietic engraftment, there was an increase in acute GVHD. There was no clear benefit in relapse rate and no evidence that transplantation with PBSC benefits patient survival in our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…aGVHD is the cause of death in up to 14% of unrelated alloHSCT (7) and up to 50% of these patients will die within 2 years of aGVHD diagnosis (13). In the alloHSCT Unit of HC-UFMG, alemtuzumab given before conditioning regime effectively reduced aGVHD (grades 2–4), compared to our historical control (12) and to patients not receiving alemtuzumab. Recent studies show a decrease in aGVHD development risk in patients treated with alemtuzumab when compared to patients receiving antithymocyte globulin (ATG) or standard prophylactic drugs, such as cyclosporine/tacrolimus and MTX (6,10,1416).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…aGVHD is the cause of death in up to 14% of unrelated alloHSCT (7) and up to 50% of these patients will die within 2 years of aGVHD diagnosis (13). In the alloHSCT Unit of HC-UFMG, alemtuzumab given before conditioning regime effectively reduced aGVHD (grades 2–4), compared to our historical control (12) and to patients not receiving alemtuzumab. Recent studies show a decrease in aGVHD development risk in patients treated with alemtuzumab when compared to patients receiving antithymocyte globulin (ATG) or standard prophylactic drugs, such as cyclosporine/tacrolimus and MTX (6,10,1416).…”
Section: Discussionmentioning
confidence: 61%
“…We have previously shown that, using a conventional GVHD prophylaxis with cyclosporine and methotrexate, incidence of grade 2–4 aGVHD was higher than expected in our center and resulted in lower survival (12). In order to reduce incidence of aGVHD and increase survival, we modified our GVHD prophylaxis strategy, and included alemtuzumab for patients with non-malignant diseases, for unrelated alloHSCT and for patients with a higher risk of TRM (i.e., older patients and/or with comorbidities).…”
Section: Introductionmentioning
confidence: 74%
“…PBSC transplantation is associated with faster blood cell and immunity recoveries. However, PBSC transplantation has also been found to be associated with increased aGVHD incidence and severity [9]. The mobilization of the peripheral blood grafts contain more T-cells than marrow suggesting a potential for development of the GVHD [19].…”
Section: Discussionmentioning
confidence: 99%
“…These disturbances potentially can stimulate a massive release of inflammatory cytokines [3]. First, baseline circulating inflammatory cytokines, such as tumor necrosis recipient age, GVHD and cytokine production [9,10]. The purpose of this study was to investigate the impact of cytokine levels (IL-1β, IL-6, IL-10, IFN-γ and TNF-α) and HCMV load in the saliva and blood, before and after allo-HSCT, on recipient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Continued efforts have been made to prevent the occurrence of severe GVHD by eliminating or suppressing donor-derived effector T cells. Conventional immunosuppression does not adequately prevent GVHD, especially in mismatched transplants (26,27). Unfortunately, elimination of donor-derived T cells impairs stem cell engraftment and delays immunologic reconstitution, rendering the recipient susceptible to posttransplantation infections and disease relapse with potentially lethal consequences.…”
Section: Discussionmentioning
confidence: 99%